International review of cytology. Volume 187 : a survey of cell biology - Jeon, Kwang W.; ScienceDirect eBooks ([Place of publication not identified] : Academic Press, 1999)
International Review of Cytology presents current advances and comprehensive reviews in cell biology-both plant and animal. Articles address structure and control of gene expression, nucleocytoplasmic interactions, control of cell development and differentiation, and cell transformation and growth. Authored by some of the foremost scientists in the field, each volume provides up-to-date information and directions for future research.
Includes index.
Online resource; title from publisher's Web site (ScienceDirect, viewed on June 4, 2012).
Elsevier
Keywords: Cytology; Cytology; Electronic books